Molecular Dynamics Study of Hydrogen on Alkali-Earth Metal Cations Exchanged X Zeolites - Du Xiaoming (International Journal of Chemical Engineering)
The self-diffusion of hydrogen in Ca2+-, Mg2+- and Ba2+-exchanged X zeolites (Mg46X, Ca46X, and Ba46X) has been studied by molecular dynamics (MD) simulations for various temperatures and loadings. The results indicate that in the temperature range of 77–298 K and the loading range of 1–80 molecules/cell, the self-diffusion coefficients are found to range from 1.2×10-9 m2·s−1 to 2.3×10-7 m2·s−1 which are in good agreement with the experimental values from the quasielastic neutron scattering (QENS) and pulse field gradients nuclear magnetic resonance (PFG NMR) measurements. The self-diffusion coefficients decrease with loading due to packing of sorbate-sorbate molecules which causes frequent collusion among hydrogen molecules in pores and increases with increasing temperature because increasing the kinetic energy of the gas molecules enlarges the mean free path of gas molecule. The mechanism of diffusion of hydrogen molecules in these zeolites is transition diffusion. Knudsen diffusion occurs at low loading and the molecular bulk diffusion occurs at higher loading. For given temperature and loading, the self-diffusion coefficients decrease in the order Ba46X<Mg46X<Ca46X, due to the different sizes and locations of the divalent cations. Moreover, the effect of concentration of molecular hydrogen on self-diffusion coefficient also is analyzed using radial distribution function (RDF).